Homo figurativus versus homo politicus – rozważania na temat kryzysu polityczności - Olbromski, Cezary Józef (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The paper refers to two apparently unrelated situations, that of a political crisis and a crisis of politicality. The author attempts to provide evidence for the fact that the etiology of these crisis situations is related to the democratic paradigm being exhausted. The combination of the instrumental and teleological activity of the actors is decisive for the content of mobilization, which is one of the fundamental reasons for both political crises and the crisis of politicality.